PENINGKATAN KESADARAN POSTUR DAN UKURAN TUBUH ANAK SEKOLAH DASAR MELALUI EDUKASI ANTROPOMETRI BERBASIS PRAKTIK - Qurbah, Hardina Atsilia; Prasetya, Ardian Jaya; Deskawainda, R. Jaler Anggerjundha; Shafa, Raihanah Muthi’ah; Rizal, Ihya Ulumuddin; Burhanudin, Syahrul Akbar; Aldyansyah, Aldyansyah (Universitas Mataram, 2026)
Learning discomfort could cause long-term musculoskeletal complaints because school students were not aware of their posture while studying and did not understand their body measurements. By using a practice-based learning approach in the classroom, this community service activity aimed to increase students' awareness of their posture and basic understanding of anthropometry. This activity was attended by 17 third-grade students at Hang Tuah 7 Elementary School in Surabaya. The methods used included visual presentations of ergonomics material, anthropometric measurement practice by students in pairs, and evaluation of understanding through games (post-test). The results of the activity showed that students were able to measure height, sitting height, arm length, and leg length with minimal guidance, and obtained relevant anthropometric data to assess the suitability of learning furniture. The evaluation showed a significant increase in understanding, marked by the students' ability to identify the correct sitting posture and apply it directly. Overall, this activity succeeded in increasing students' awareness of ergonomics and provided practical recommendations for schools in arranging furniture based on children's anthropometry.